Multitude : - Divakaruni, Chitra Banerjee (McGraw-Hill, 1997)
Known for its upbeat approach, MULTITUDE brings together a diverse spectrum of voices and issues that reflect our society. This anthology is divided into 10 broad themes and provides a variety of perspectives on the ways people connect across boundaries of ethnicity, class, gender, age, and geography. The 84 readings include essays, student essays, fiction, poetry, letters, and journals and includes a diversity of lengths and difficulty. The second edition features 40% new selections and more writing activities and assignments that incorporate collaboration and research.